Analysis of maxillofacial injuries caused by the 2010 Yushu earthquake in China. Issue 9 (13th October 2011) - Guo, Lijuan; Guo, Weihua; Li, Rui; Sheng, Lei; Yang, Bo; Tang, Wei; Liu, Lei; Jing, Wei; Wang, Hang; Tian, Weidong
Abstract : Background: The condition of maxillofacial injuries after a major earthquake is not well understood because of limited data. The purpose of this study was to describe the maxillofacial injuries caused by the 2010 Yushu earthquake in China. Methods: A total of 126 patients treated for seismic-related injuries at hospitals in the Chengdu area were investigated. Of the 126 patients, 46 (36.5%) had maxillofacial injuries. Gender, age, nationality and injury condition were recorded by talking with the patients and their families. The data were analysed using Microsoft Access 2003 and SPSS software programs. Results: For the 46 patients, the female to male ratio was 1.3:1 and the mean age was 36.7 years. Most patients (41, 89.1%) were Tibetan. The most frequent cause of maxillofacial injury was pressing/burying (34 patients, 73.9%). All patients with maxillofacial injuries sustained soft-tissue injuries, 13.0% had facial fractures and 4.3% had dentoalveolar injuries. The soft-tissue injuries were largely combined injuries; 84.8% were bruises and 80.4% were lacerations. The most common injury site was the zygomatic region (54.3%), followed by the forehead (43.5%) and the orbital region (34.8%). Of the six facial fractures, four involved nasal–orbital–ethmoidal region fractures. Most of the maxillofacial injuries (78.3%) were associated with other injuries, of which extremity injuries (55.6%) were the most common. Conclusion: An analysis of the maxillofacial injuries sustained during the Yushu earthquake revealed some of the features of seismic-related maxillofacial injuries. The results from this study may help physicians provide better medical services during future disasters.